2018
DOI: 10.1002/bio.3492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity and dielectric constant variation on fractional fluorescence quenching analysis of coumarin dye in binary solvent mixtures

Abstract: Photo physical properties of fluorescent organic compounds give an immense improved knowledge on characteristics of excited state that is beneficial to devise innovate molecules and understand their performance in particular applications. Coumarin derivatives have been extensively investigated in this regard. This article narrates steady state fluorescence quenching measurements of a coumarin derivative namely 3-hydroxy-3-[2-oxo-2-(3-oxo-3H-benzo[f]chromen-2-yl)-ethyl]-1,3-dihydro-indol-2-one (3HBCD) in a bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 46 publications
(111 reference statements)
2
24
0
Order By: Relevance
“…In some cases, it has been observed that certain quenching reactions give curved S–V plots. Both upward and downward curves have been observed by many researchers. While positive curvature is associated with various processes such as combined static and dynamic quenching, intersystem crossing, or the formation of charge transfer complexes at ground and excited states, negative curvature in S–V plots is due to the heterogeneity of the system, selective quenching, hydrogen bond complex formation, or occurrence of a reversible photochemical process.…”
Section: Theorymentioning
confidence: 84%
“…In some cases, it has been observed that certain quenching reactions give curved S–V plots. Both upward and downward curves have been observed by many researchers. While positive curvature is associated with various processes such as combined static and dynamic quenching, intersystem crossing, or the formation of charge transfer complexes at ground and excited states, negative curvature in S–V plots is due to the heterogeneity of the system, selective quenching, hydrogen bond complex formation, or occurrence of a reversible photochemical process.…”
Section: Theorymentioning
confidence: 84%
“…The K sq value can be used to quantitatively determine the ability of the complex to interact with the DNA under the same conditions. The greater the K sq value, the stronger the ability . The emission spectra of EtBr bound to DNA in the absence and presence of the two complexes and the fluorescence‐quenching curve are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Data related to positive S-V plot is pursued using modified S-V equations 15 . Negative deviation of S-V plots (downward curvature) is also reported by many researchers 10,13,14,16 . Many Reasons such as heterogeneity of the system, selective quenching, hydrogen bond complex formation, occurrence of reverse reaction in photochemical process etc are identified for the negative deviation.…”
Section: Theorymentioning
confidence: 89%
“…Many Reasons such as heterogeneity of the system, selective quenching, hydrogen bond complex formation, occurrence of reverse reaction in photochemical process etc are identified for the negative deviation. Quenching data which are expected to arise from one of these reasons may be represented by modified 'SternVolmer' equation or Lehrer equation 10,17,18 given below. In the present paper we report the quenching of a newly synthesized Quinolin-8-ol (QO) in toluene and butanol solvents.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation